Associations between physial activity and thyroid function - Ślusarska, Aleksandra; Błasiak, Paulina; Mikołajec, Patryk; Bilecka, Barbara; Mędyk, Jolanta; Wirkijowska, Małgorzata; Patarocha, Yauheniya; Rogulski, Michał; Huk, Ruslan (Quality in Sport, 2025)
Disorders related to thyroid hormone regulation are among Poland’s leading reasons for endocrinological consultations. The diagnosis and monitoring of thyroid dysfunction primarily rely on blood tests, including the measurement of TSH, fT3, and fT4 hormone levels, as well as antibodies specific to autoimmune thyroid diseases, such as anti-TPO, anti-Tg, and anti-TSHR. These tests are also useful in evaluating the impact of various factors on thyroid metabolism. In our study, we analyzed the effect of physical activity on thyroid function, taking into account specific population groups and particular disease entities.